2011
DOI: 10.1021/ic201340m
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Active Species and Mechanism of Cytotoxicity of Salan-Ti(IV) Complexes: A Stereochemical Study

Abstract: Following the discovery of cisplatin, much effort has been devoted to the exploration of transition metal complexes as cytotoxic agents. We have recently introduced the highly efficient C(2)-symmetrical salan-Ti(IV) family of complexes, demonstrating high cytotoxicity toward colon and ovarian cells and enhanced hydrolytic stability in mixed organic/water solutions. The effect of stereochemistry is hereby reported, by comparing the cytotoxic activity and hydrolysis of pure enantiomers and their racemic mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
58
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 36 publications
12
58
2
Order By: Relevance
“…HBED is a cell-permeable molecule that is a promising candidate for iron-overload disease therapy because of its high Fe(III) affinity (41). Ti(IV) compounds of diamine-bis(phenolato) ligands, which are related to HBED but lack the carboxylate appendages, display cytotoxic properties in different cell lines in vitro (14,17,19,28,(42)(43)(44) and in a mouse cancer model in vivo (35). It is feasible that Ti(IV) compounds of citrate and HBED could use ligand-specific mechanisms for transport into cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HBED is a cell-permeable molecule that is a promising candidate for iron-overload disease therapy because of its high Fe(III) affinity (41). Ti(IV) compounds of diamine-bis(phenolato) ligands, which are related to HBED but lack the carboxylate appendages, display cytotoxic properties in different cell lines in vitro (14,17,19,28,(42)(43)(44) and in a mouse cancer model in vivo (35). It is feasible that Ti(IV) compounds of citrate and HBED could use ligand-specific mechanisms for transport into cells.…”
Section: Resultsmentioning
confidence: 99%
“…Another study shows that substitutions ortho to the binding phenolato unit of salan-type ligands influences the cytotoxicity of these types of Ti(IV) compounds because of electronic and steric effects (27). In addition, both the chirality of ligands (28) and ligand coordination to Ti(IV) (28,29) can affect the cytotoxicity of Ti(IV) compounds.…”
mentioning
confidence: 99%
“…However, recent advances in titanium-stabilizing ligands have led to a new class of cytotoxic Ti-based antineoplastics 5 . Prominently, introduction of the ligand salan, a diamine bisphenalato compound, conferred excellent hydrolytic stability to Ti(IV) alkoxide complexes, as presented by Tshuva and co-workers (Chart 1, 1) [6][7][8][9][10][11][12][13] . Many of these compounds also demonstrated micro-and submicromolar antiproliferative activity against HT29 and OVCAR-1 cancer cell lines in vitro.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Complexes of Ti IV , budotitane ((bzac) 2 Ti(OEt 2 ), titanocene dichloride (Cp 2 TiCl 2 ) and their derivatives exhibited high anti-cancer properties against a range of cell lines with relatively minor side effects; nevertheless, rapid hydrolysis of the complexes in biologically relevant solutions to multiple unidentified species inhibited their utility [2][3][4][5][6][7][8][9][10][11][12][13]. Previously we have presented the diaminobis(phenolato) Ti IV complexes with particularly high cytotoxic activity, demonstrating higher hydrolytic stability than that of budotitane and titanocene dichloride [14][15][16][17][18][19][20][21][22][23][24][25]. Structure-activity relationship studies revealed that, for example, methyl groups on the nitrogen atoms (N-Me) greatly improve the hydrolytic stability of the complexes compared with no substitution (N-H) [22].…”
mentioning
confidence: 99%
“…Structure-activity relationship studies revealed that, for example, methyl groups on the nitrogen atoms (N-Me) greatly improve the hydrolytic stability of the complexes compared with no substitution (N-H) [22]. Subsequent studies suggested that the active species are polynuclear O-bridged hydrolysis products [26]: trinuclear species for N-Me complexes [15,16] and binuclear species for N-H complexes [22,23], thus eliminating the need for labile ligands. The polynuclear hydrolysis products mostly showed anticancer activity only in particular nano-formulations, due to diminished accessibility and solubility [26,27].…”
mentioning
confidence: 99%